Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/ele.13915
|View full text |Cite
|
Sign up to set email alerts
|

Sampling bias exaggerates a textbook example of a trophic cascade

Abstract: Knowledge about the occurrence and strength of trophic cascades (indirect effects of predators on plants and abiotic processes) is vital to understand the forces that structure food webs. Much of the empirical information about trophic cascades derives from tractable systems that are variously small scale, aquatic, invertebrate and captive (Alston et al., 2019; Ford & Goheen, 2015;Piovia-Scott et al., 2017). Less is known about trophic cascades in terrestrial wildlife systems due in part to the difficulty and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…This does not mean the mechanisms cannot co-occur in predator-prey systems, as is often the case with density-and trait-mediated indirect effects (Peacor & Werner 2001;Preisser et al 2005;Pruett & Weissburg 2021;Werner & Peacor 2003). For example, in Yellowstone National Park, wolves affected both the population density (Peterson et al 2014;Vucetich et al 2005) and, to a lesser degree, space use of elk (Cervus canadensis) (Cusack et al 2019;Kohl et al 2018), which had a weak but measurable cascading effect on aspen (Populus tremuloides) recruitment (density-and trait-mediated effects; (Brice et al 2022). But wolf-killed elk carcasses also have PIEs on local plant and soil communities (Risch et al 2020) that would occur regardless of whether wolves altered elk density or traits.…”
Section: Discussionmentioning
confidence: 99%
“…This does not mean the mechanisms cannot co-occur in predator-prey systems, as is often the case with density-and trait-mediated indirect effects (Peacor & Werner 2001;Preisser et al 2005;Pruett & Weissburg 2021;Werner & Peacor 2003). For example, in Yellowstone National Park, wolves affected both the population density (Peterson et al 2014;Vucetich et al 2005) and, to a lesser degree, space use of elk (Cervus canadensis) (Cusack et al 2019;Kohl et al 2018), which had a weak but measurable cascading effect on aspen (Populus tremuloides) recruitment (density-and trait-mediated effects; (Brice et al 2022). But wolf-killed elk carcasses also have PIEs on local plant and soil communities (Risch et al 2020) that would occur regardless of whether wolves altered elk density or traits.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of replication and difficulty of isolating trait‐mediated from density‐mediated factors, there is contrasting evidence regarding trait‐mediated trophic cascade effects on communities, ungulate populations, and ungulate physiology. Moreover, recent work highlighted concerns with sampling design that affected the strength of a trophic cascade in the Greater Yellowstone Ecosystem (Brice et al, 2022). Studies on trait‐mediated trophic cascades in particular suffer from the taxonomic and regional biases mentioned previously because they tend to be focused on cursorial predators in the Greater Yellowstone Ecosystem, likely due to the natural experiment provided by the reintroduction of wolves (Bleicher, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent work highlighted concerns with sampling design that affected the strength of a trophic cascade in the Greater Yellowstone Ecosystem (Brice et al, 2022). Studies on trait-mediated trophic cascades in particular suffer from the taxonomic and regional biases mentioned previously because they tend to be focused on cursorial predators in the Greater Yellowstone Ecosystem, likely due to the natural experiment provided by the reintroduction of wolves (Bleicher, 2017).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Many previous authors have noted that the biodiversity trends observed in a monitoring scheme are highly sensitive to sampling methodology [26,40,[79][80][81][82][83][84]. For example, in a European bumble bee survey the three methods used all produced different estimates of the population [79].…”
Section: Discussionmentioning
confidence: 99%